Engineering NiCo2S4 nanoparticles anchored on carbon nanotubes as superior energy-storage materials for supercapacitors. Issue 54 (6th December 2022) - Chen, Junming; Du, Zhiling; Cheng, Kun; Bao, Jusheng; Wang, Guiling; Yao, Yue; Song, Jiayi; Yue, Jing; Xu, Kun; Xie, Weicheng; Qiang, Wei; Liu, You; et al.
Abstract : A one-step hydrothermal method was used to successfully synthesize NiCo2 S4 nanocomposites anchored on carbon nanotubes as excellent energy storage materials for supercapacitors. Abstract : Fabricating high-capacity electrode materials toward supercapacitors has attracted increasing attention. Here we report a three-dimensional CNTs/NiCo2 S4 nanocomposite material synthesized successfully by a facile one-step hydrothermal technique. As expected, a CNTs/NiCo2 S4 electrode shows remarkable capacitive properties with a high specific capacitance of 890 C g −1 at 1 A g −1 . It also demonstrates excellent cycle stability with an 83.5% capacitance retention rate after 5000 cycles at 10 A g −1 . Importantly, when assembled into a asymmetric supercapacitor, it exhibits a high energy density (43.3 W h kg −1 ) and power density (800 W kg −1 ). The exceptional electrochemical capacity is attributed to the structural features, refined grains, and enhanced conductivity. The above results indicate that CNTs/NiCo2 S4 composite electrode materials have great potential application in energy-storage devices.